Investment in a Smaller World: The Implications of Air Travel for Investors and Firms - Da, Zhi; Gurun, Umit G.; Li, Bin; Warachka, Mitch (Management Science, 2021)
A large literature reports that proximity influences investment. We extend the measurement of proximity beyond distance and report that air travel reduces local investment bias. This result is confirmed using the initiation of connecting flights through recently opened air hubs because investment at destinations served by these connecting flights increases after, not before, their initiation. Air travel also broadens the investor base of firms and lowers their cost of equity by approximately 1%. Overall, air travel improves the diversification of investor portfolios and lowers the cost of equity for firms. This paper was accepted by Tyler Shumway, finance.